Bagha Jatin : Life in Bengal and Death in Orissa (1879-1915) - Mukherjee, Prithwindra (Brill | Manohar Publishers & Distributors, 2016)
Bagha Jatin, alias Jatindranath Mukherjee, is one of our legendary figures in the history of revolutionary efforts in India. The truth of this matter is unfortunately shrouded in inaccurate tales. Bagha Jatin was involved in the German Conspiracy Plot during the First World War, hoping to get arms from the Germans for a country-wide rising, but died fighting with the British army and police before the arms could arrive. We now know from this factually accurate account of the last phase in his career written by his grandson that the Tiger had a very sophisticated understanding of the contemporary political reality. He was not hoping to overthrow the British power in India by one single revolutionary action, but hoped to inspire his countrymen with the ideal of self-sacrifice in the cause of independence and by his own martyrdom infuse them with courage. This accurate description of his struggle with the ruling colonial power shows the nature of the initiative and also the impact it had on the national psyche. In short, it is a great book. - Tapan Raychaudhuri, Emeritus Fellow, St. Antony's College, Oxford / Professor of Indian History and Civilization, University of Oxford